Public Perception and Adaptation to Climate Change in Moro Local Government, Kwara State, Nigeria - O. O. Salami; F. O. Rafiu; M. A. Akanbi-Gada; S. Walliyyulahi (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to evaluate the public perception and adaptation to climate change in Moro Local Government, Kwara State, Nigeria. A total of 60 questionnaires were administered across five settlements. Findings revealed that 45% of respondents had heard about climate change, though awareness levels varied, with Igbo Oreku showing the highest awareness (11.7%) and Okete the lowest (3.3%). About 90% of respondents acknowledged changes in rainfall patterns and temperature, which significantly had impact on their agricultural operations. Majority (75%) noted that the dry season had lengthened, and 78.3% observed a shift in planting times due to reduced rainfall. While only 40% acknowledged contributing to climate change through deforestation, 46.7% were willing to adopt adaptation strategies like reducing wood burning and participating in environmental campaigns. The study concludes that climate change adaptation must address local socioeconomic realities and be supported by targeted policies. Recommendations include increasing public awareness through local government-led education programs, promoting sustainable practices, and enhancing collaboration between local authorities, NGOs and communities.